Is it Possible for Intelligent Automata to Exist? - Davidavičius, Algis (Problemos, 2002)
This article deals primarily with the logical and the factual possibilities for automata to become persons and in that sense intelligent beings. It is argued here, that there are no strong logical arguments against conceivability of possible existence of such entities. This existence is logically possible, if we rely on special kind of epistemologically relevant property dualism, coupled with a broader ontological monism and a functional definition of a person. It is argued later, that factual realizability of those possible technogenous persons is strongly dependent on special ontological commitment to the realization of such possibility. The arguments and analysis provided are mostly based on David Chalmers's views and their direct critique by other authors.
Keywords: person; intelligent; automata; identity of counsciousness; ontological commitment; ontological monism